Rules, discretion or reputation? Monetary policies and the efficiency of financial markets in Germany, 14th to 16th centuries - Oliver Volckart (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
This paper examines the questions of whether and how feudal rulers were able to credibly commit to preserving monetary stability, and of which consequences their decisions had for the efficiency of financial markets. The study reveals that princes were usually only able to commit to issuing a stable coinage in gold, but not in silver. As for silver currencies, the hypothesis is that transferring the right of coinage to an autonomous city was the functional equivalent to establishing an independent central bank. An analysis of market performance indicates that financial markets between cities that were autonomous with regard to their monetary policies were significantly better integrated and more efficient than markets between cities whose currencies were supplied by a feudal ruler.
Keywords: G15; N13; N23; N43; 330; Financial markets; integration; monetary policy; Middle Ages; Regionaler Finanzmarkt; Marktintegration; Markteffizienz; Geldpolitik; Geldgeschichte; Feudalismus; Deutschland (bis 1945)